The effect of warm water compresses with cinnamon (cinnamomum) powder on pain scales of gout arthritis in the elderly: A pre-experimental study - Della Friska Putri; Muhammad Romadhon; Sasono Mardiono; Ranida Arsi (Lentera Perawat, 2025)
Background: Joint pain is a common complaint experienced by many people, especially the elderly. One of the non-pharmacological methods that can be used to reduce pain is warm water compress therapy using cinnamon powder (Cinnamomum). This compress provides a warming effect that can decrease muscle spasms, improve blood circulation, and help suppress the inflammatory response in the joint area. Objective: This study aimed to determine the effect of a warm water compress with cinnamon powder (Cinnamomum) on changes in the pain scale of gout arthritis among the elderly at Bukit Selabu Sekayu Public Health Center. Methods This research used a pre-experimental design with a One Group Pre-Test Post-Test approach. The sample consisted of 35 elderly respondents, selected through total sampling. The research instruments included the Standard Operating Procedure (SOP) for administering the warm water compress with cinnamon powder and an observation sheet using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon Signed Rank Test. Results : The findings showed that the mean pain score before the intervention was 4.63 (moderate pain category), and after the warm water compress with cinnamon powder was applied, it decreased to 1.97 (mild pain category). The statistical test obtained a p-value = 0.000 (p < 0.05), indicating a significant difference between pre- and post-intervention. A 2.66-point reduction on the NRS was considered clinically meaningful, showing that this therapy effectively reduced joint pain in the elderly. Conclusion: The application of a warm water compress with cinnamon powder (Cinnamomum) was proven to be statistically and clinically effective in reducing joint pain levels among elderly patients with gout arthritis. This therapy can serve as a safe and practical non-pharmacological alternative that can be applied in primary health care services.